Promoting Competence and Confidence: Simulation-Based Basic Life Support Training for Jordanian Nurses - Yousef Shukry Abu-Wardeh; Wan Muhamad Amir W Ahmad; Mohd Shaharudin Shah Che Hamzah; Intan Idiana Hassan (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Cardiopulmonary arrest is a major health issue that affects healthcare providers. The COVID-19 pandemic has added a new risk to rescuers who may be attempting to resuscitate victims. It is essential to strike a balance between resuscitation and the need to protect oneself from infection. The study aims to evaluate the effectiveness of simulation training in enhancing the Basic Life Support (BLS) knowledge, skills, and confidence levels of newly employed nurses. The study employed a single-masked, prospective, randomized controlled trial design, which consisted of three phases: a pre-test, an immediate post-test, and a post-test conducted three months later. The American Heart Association’s BLS test was used to assess knowledge and practical skills of 102 nurses who were randomly assigned to two groups. The nurses' con-fidence was evaluated through a self-evaluation questionnaire. The control group received the brochure, and the inter-ventional group received a seven-hour BLS training using simulation. Both arms were homogenous in their characteris-tics, according to Mann-Whitney analysis. Independent T-test reflected homogenous pre-test results in knowledge, prac-tice, and confidence between both arms. The result also showed significant differences between both groups in the post-test-1 in knowledge (p < 0.001), practice (p < 0.001) and confidence (p = 0.024); and significant differences in the post-test-2 between both groups in knowledge (p < 0.001), practice (p = 0.002) and confidence (p < 0.001). BLS training using simulation is an efficient method that enables participants to become more knowledgeable and skilled in BLS, resulting in a high level of confidence. Frequent, short BLS training using simulation helps maintain competence and confidence, ensuring readiness for CPR in case of cardiopulmonary arrest. Keywords: basic cardiac life support, confidence, knowledge, practice, simulation training Abstrak Mempromosikan Kompetensi dan Kepercayaan Diri: Pelatihan Bantuan Hidup Dasar Berbasis Simulasi bagi Perawat Jordania. Henti jantung paru adalah masalah kesehatan utama yang memengaruhi penyedia layanan kesehatan. Pandemi COVID-19 menambah risiko bagi tim penyelamat yang berupaya menyadarkan korban. Penting menyeimbangkan kebutuhan resusitasi dengan perlindungan diri dari infeksi. Penelitian ini mengevaluasi efektivitas pelatihan simulasi dalam meningkatkan pengetahuan, praktik, dan kepercayaan diri perawat baru. Studi ini menggunakan desain single-masked prospective randomized control trial yang terdiri dari tiga fase: pre-test, post-test segera setelah intervensi, dan post-test yang dilakukan tiga bulan kemudian. Tes Basic Life Support (BLS) dari American Heart Association digunakan untuk menilai pengetahuan dan keterampilan praktik. Selain itu, kepercayaan diri perawat dievaluasi melalui kuesioner evaluasi diri. Seratus dua perawat didistribusikan acak ke dua kelompok; kontrol menerima brosur, intervensi menerima pelatihan BLS tujuh jam menggunakan simulasi. Kedua kelompok memiliki karakteristik homogen dengan analisis Mann-Whitney. Uji-T independen menunjukkan hasil pra-tes homogen dalam pengetahuan (p = 0,324), praktik (p = 0,887) dan kepercayaan diri (p = 0,304). Hasil menunjukkan perbedaan signifikan pada post-test-1 dalam pengetahuan (p < 0,001), praktik (p < 0,001) dan kepercayaan diri (p = 0,024); serta post-test-2 dalam pengetahuan (p < 0,001), praktik (p = 0,002) dan kepercayaan diri (p < 0,001). Pelatihan BLS dengan simulasi adalah metode efisien yang meningkatkan pengetahuan, keterampilan, dan kepercayaan diri peserta dalam BLS. Pelatihan BLS singkat dan sering menggunakan simulasi membantu menjaga kompetensi dan kepercayaan diri, memastikan kesiapan untuk CPR jika terjadi henti jantung dan paru. Kata Kunci: bantuan hidup jantung dasar, kepercayaan diri, pelatihan simulasi, pengetahuan, praktik